2015
DOI: 10.1074/jbc.m114.603555
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal Plasma Activates Human Keratinocytes by Stimulation of Antioxidant and Phase II Pathways

Abstract: Background: Non-thermal plasma provides an interesting therapeutic opportunity to control redox-based processes, e.g. wound healing. Results: The transcription factor NRF2 and downstream signaling molecules were found to act as key controllers orchestrating the cellular response. Conclusions: Plasma triggers hormesis-like processes in keratinocytes. Significance: These findings facilitate the understanding of plasma-tissue interaction and its deduced clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
88
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 87 publications
9
88
0
1
Order By: Relevance
“…For microscopic evaluation, cells were seeded in 6-well plates and grown to 80 % confluence in DMEM prior to indirect plasma treatment. Twenty-four hours after exposure to plasma treated medium, apoptotic cells were stained using terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL)-technique as previously described [13].…”
Section: Metabolic Activity and Microscopic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…For microscopic evaluation, cells were seeded in 6-well plates and grown to 80 % confluence in DMEM prior to indirect plasma treatment. Twenty-four hours after exposure to plasma treated medium, apoptotic cells were stained using terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL)-technique as previously described [13].…”
Section: Metabolic Activity and Microscopic Evaluationmentioning
confidence: 99%
“…In human keratinocytes we have previously demonstrated a cold plasma-mediated modulation of the metabolic activity of cells, and an alteration of their antioxidant defense [12]. Plasma also triggered hormesis-like processes trough the Nrf2 pathway and thus prepared skin cells against exogenic noxae by increasing their resilience against oxidative species [13].…”
Section: Introductionmentioning
confidence: 98%
“…NTAPP has also been reported to accelerate wound healing processes by activating the nuclear factor erythroid-related factor 2 (NRF2) signaling pathway in human keratinocyte HaCa T cell line in vitro 19, and to promote re-epithelialization and wound closure by activating keratinocytes and fibroblasts in Wistar rats’ wound skin20. These studies strongly suggested that NTAPP stimulates the proliferation of normal and adult stem cells.…”
mentioning
confidence: 97%
“…Some reports indicate that NAP can enhance the proliferation rate of basal keratinocytes and endothelial cells [75,76] . The 350 downregulated and 400 upregulated transcripts of keratinocytes after NAP treatment highlighted its powerful ability to influence gene expression [77] .…”
Section: Hydrogen Peroxide: Implications For Chronic Wound Treatmentmentioning
confidence: 99%